KERAGAAN BENIH HORTIKULTURA DI TINGKAT PRODUSEN DAN KONSUMEN (Studi kasus : Bawang merah, Cabai merah, Kubis dan Kentang) - DARWIS, VALERIANA; IRAWAN, BAMBANG; MUSLIM, CHAERUL (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Seed and seedling is one of main factors in determining the product of horticultural crops. The use seed production on horticultural crops, could be produced by government institution or private sector. In the last 21 years (1980 – 2001) the government has released 183 improved variety of vegetables, including 26 red onion, red chili, cabbage and potato. These number is much Owen compared to number of improved variety of crops. For instance 105 new improved varieties for rice, 50 varieties for corn and 33 varieties for soybean. The role of private sectors on the horticultural seed is much more dominant to the high demand commodities and cannot be produced by the farmers it can be seen on the production of red chili seed compared to three other commodities. The performance of seed on the level consumer, represented by the farmers in the area production central, namely red onion, red chili in the central Java Province, and potato and cabbage in North Sumatera Province. The findings of the study are : the farmers are influencing by the group on the selection of seed to be use, the role of field extension worker is very limited, the seed has been use by the farmers before introducing by government, at any planting time the farmers not always use a new seed, even there are some farmers never used improved variety of potato.
Keywords: Horticultural Seed, Producer and Consumer